Peranan Sumber Daya Manusia dalam Organisasi - Maulana, Burhan; Iyon Cahyono; Juliandri Johan; Muzhar Khotib; Tanit Prayitno; Wahyu Wiguna (IPM2KPE, 2026)
This study aims to analyze the strategic role of human resources (HR) in organizations and how the management of HR functions contributes to the achievement of company goals and operational success effectively and efficiently. The research method used is a descriptive qualitative approach with library research, involving the identification, selection, and comparative analysis of relevant scientific literature and textbooks published between 2021 and 2025. The results indicate that HR plays a key role in driving organizations through the implementation of workforce planning, appropriate recruitment and selection, competency development through training, performance management, and the provision of competitive compensation and benefits. Furthermore, synergy between the HR department and line managers in fostering organizational culture has been shown to increase employee flexibility and engagement. The study concludes that HR is the most valuable asset and key to an organization's competitive advantage; optimizing individual potential through holistic and technology-adaptive management is crucial to achieving superior, inclusive, and sustainable organizational performance in the digital age. Keywords: Human Resources, Organizational Management, Employee Development, HR Strategy, Organizational Performance